An automated colorimetric inline titration of CO2 concentrations in solvent flow streams using a Teflon AF-2400 tube-in-tube device. (October 2017) - O'Brien, Matthew
Abstract: Using a number of open source software components (Python, SciPy, OpenCV, PySerial), together with an inexpensive webcam device, an automated inline colorimetric titration methodology was developed to measure CO2 concentration levels in organic flow streams emerging from a Teflon AF-2400 tube-in-tube device. A bisection search algorithm was used in combination with a curve-fitting approach to determine colorimetric titration endpoints. The results obtained are consistent with a simple 'negative exponential' model of permeation/dissolution.